2015
DOI: 10.1186/s12864-015-2201-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative miRNAs analysis of Two contrasting broccoli inbred lines with divergent head-forming capacity under temperature stress

Abstract: BackgroundMicroRNAs (miRNAs) play a vital role in growth, development, and stress response at the post-transcriptional level. Broccoli (Brassica oleracea L. var italic) is an important vegetable crop, and the yield and quality of broccoli are decreased by heat stress. The broccoli inbred lines that are capable of producing head at high temperature in summer are unique varieties in Taiwan. However, knowledge of miRNAomes during the broccoli head formation under heat stress is limited.MethodsIn this study, molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 67 publications
(100 reference statements)
5
27
0
Order By: Relevance
“…Seven of the sixty-one lncRNAs were differentially expressed lncRNAs between Brassica allohexaploid and its parents. We checked the sequences of lncRNAs to screen out miRNA precursors and found that only 15 of 3,120 lncRNAs (0.48%) harbored complete precursors for 15 miRNAs (Table S11), which was consistent with the earlier study that only 0.2% of lncRNAs serve as miRNA precursors to regulate biological processes (Chen, Fu et al, 2015;Chen, Quan, & Zhang, 2015). Prediction of the secondary structure for the 15 transcripts using the Vienna RNA package RNAfold program showed that these miRNA precursors had stable hairpin structures ( Figure S4), two of which are shown in Figure 14.…”
Section: Lncrna As Targets Of Mirnas and As Mirnas Precursorssupporting
confidence: 89%
See 4 more Smart Citations
“…Seven of the sixty-one lncRNAs were differentially expressed lncRNAs between Brassica allohexaploid and its parents. We checked the sequences of lncRNAs to screen out miRNA precursors and found that only 15 of 3,120 lncRNAs (0.48%) harbored complete precursors for 15 miRNAs (Table S11), which was consistent with the earlier study that only 0.2% of lncRNAs serve as miRNA precursors to regulate biological processes (Chen, Fu et al, 2015;Chen, Quan, & Zhang, 2015). Prediction of the secondary structure for the 15 transcripts using the Vienna RNA package RNAfold program showed that these miRNA precursors had stable hairpin structures ( Figure S4), two of which are shown in Figure 14.…”
Section: Lncrna As Targets Of Mirnas and As Mirnas Precursorssupporting
confidence: 89%
“…LncRNAs could act as targets or precursors of miRNAs to regulate gene expression (Chen, Fu et al., ; Chen, Quan, & Zhang, ). Target mimicry is a vital function for lncRNAs to regulate growth and metabolic progress in plants (Zhu & Wang, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations